The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1590/1807-2577.08216
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of resistance to fatigue between straight solid and anatomic abutments of Morse taper system

Abstract: ResumoContexto: O estudo do fenômeno de fadiga é essencial porque as falhas de implantes geralmente são causadas por este processo. Objetivo: O objetivo deste estudo foi analisar a resistência à fadiga de conjuntos de pilares retos e anatômicos que foram submetidos a cargas cíclicas. Material e método: Foram utilizados 37 implantes cone Morse e 37 pilares, divididos em dois grupos (n = 16: pilares retos, n = 21: pilares anatômicos). Os conjuntos foram submetidos à carga cíclica (5.000.000) usando o equipamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…According to previous study, there was no different bending moment between anatomical abutment and straight abutment. However, it was found that the longevity of anatomical abutment after fatigue test was lower than the straight abutment group [40]. In this study, both a customized titanium abutment and hybrid abutment were created with anatomical design; the connection for abutments was made with the same manufacturing.…”
Section: Discussionmentioning
confidence: 94%
“…According to previous study, there was no different bending moment between anatomical abutment and straight abutment. However, it was found that the longevity of anatomical abutment after fatigue test was lower than the straight abutment group [40]. In this study, both a customized titanium abutment and hybrid abutment were created with anatomical design; the connection for abutments was made with the same manufacturing.…”
Section: Discussionmentioning
confidence: 94%